elexiko and Discourse Dictionary: two types of online-lexicography - Kämper, H; Klosa, A (2010)
In this paper, two types of dictionaries are presented: a discourse dictionary and a general dictionary, both online in the same lexicographic portal (OWID; www.owid.de). Our aim is to show the special features of each type focussing on the semantic description and the relation between the two types. We will compare the dictionaries on the entry Demokratie, one of the most important concepts in the 20th century. Thus, Demokratie is one of the main words of the general political lexicon and has to be described in a general dictionary. At the same time, it plays an outstanding and specific role in certain public discourses over the last 100 years (e.g., 1918/19, 1945, 1989) and should be described in a discourse dictionary. The "Diskurswörterbuch 1945-55" (e.g. "Diskurswörterbuch 1945-55: Opfer-Täter-Nichttäter. Ein Wörterbuch zum Schulddiskurs 1945-1955"; http://www.owid.de/Diskurs1945-55/index.html) reconstructs the usage of the concept 'Demokratie' as an element of the discourse: with typical (often contrary) functions in relation to the participants of the discourse (.e.g., participants of western or of the eastern discourse), with special collocations (e.g., as a partner word of guilt), and above all, as a part of the discourse network that creates a semantic structure. Evidence of this can be visualized by a discourse analysis (e.g. Freiden ['peace'], Freiheit ['freedom'], Antifaschismus ['antifascicism'], Volk ['nation'], Mensch ['person']. elexiko (e.g., "elexiko - An online dictionary of contemporary German; http://www.owid.de/elexiko_/index.html) as a general dictionary gives broad semantic information for each entry: the paraphrase, paradigmatic relations (for Demokratie for example synonyms [e.g., Parlamentarismus], antonyms [e.g, Fachismus], as well as kohyponyms [e.g., Pluralismus]), and covers typical phrases (e.g., sich in Demokratie üben ['to excercise democracy'].